2017
DOI: 10.1002/hed.24703
|View full text |Cite
|
Sign up to set email alerts
|

Survey of return to work of head and neck cancer survivors: A report from a tertiary cancer center in India

Abstract: Further studies are needed to address the large unmet needs regarding identification and amelioration of barriers to return to work for head and neck cancer survivors in low- and middle-income countries, such as India. © 2017 Wiley Periodicals, Inc. Head Neck 39: 893-899, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 15 publications
(55 reference statements)
5
36
2
8
Order By: Relevance
“…Of those who did not RTW (10 of 68; 14.7%), half cited ongoing treatment-related adverse effects as the predominant obstacle to RTW. Although our results are broadly similar to those of other non-HPV HNC studies, [28][29][30] these studies have significant patient selection heterogeneity, varying with respect to tumor location, treatment modalities, and time since completing treatment. Importantly, country-specific differences in health care systems, social support, and workplace laws will significantly affect how and when patients RTW.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Of those who did not RTW (10 of 68; 14.7%), half cited ongoing treatment-related adverse effects as the predominant obstacle to RTW. Although our results are broadly similar to those of other non-HPV HNC studies, [28][29][30] these studies have significant patient selection heterogeneity, varying with respect to tumor location, treatment modalities, and time since completing treatment. Importantly, country-specific differences in health care systems, social support, and workplace laws will significantly affect how and when patients RTW.…”
Section: Discussionsupporting
confidence: 86%
“…The majority of participants in this study returned to the same occupation and hours that they worked before their diagnosis, as also seen in other HNC studies. 28,30,38 In addition, HNC studies have found that support from employers and coworkers and work flexibility and modifications helped patients to RTW, 32,38,40,51,52 as reflected in our study. In our sample, better HNC and QOL scores were associated with returning to the same or more hours of work.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…They also reported that unemployed patients experienced more anxiety because of their diagnosis and treatment and that white‐collar workers had greater fear of public contact than blue‐collar workers. However, OCC survivors who were female and had better family structure (two male children with the eldest child younger than 20 years) and more education were more likely to return to work . In addition, HNC survivors who were older, had less education, greater anxiety, greater oral dysfunction, and worse social functioning were less likely to return to work .…”
Section: Introductionmentioning
confidence: 99%